FUNGSI INTERNAL CONTROL DALAM PENCEGAHAN FRAUD DI PT BANK MANDIRI (PERSERO) TBK. REGIONAL X MAKASSAR - Dewi Andriani; Syarif Syarif; Aini Indrijawati; Syamsuddin Syamsuddin (Magister Akuntansi, Universitas Atma Jaya Makassar, 2020)
This study aims to examine and analyze the function of internal control in fraud prevention at PT Bank Mandiri (Persero) Tbk. Regional X Makassar. This research uses descriptive qualitative analysis method where the data is obtained based on the results of interviews and adapted so that it becomes data that is explaining the research issue. The results of this study indicate that Bank Mandiri in Regional X Makassar continues to be committed and proactive with good governance in fraud prevention, with a special Internal Control unit that handles this and reports directly to the CEO in Regional / Independent. By way of prevention; Creating an Honest Culture and Eliminating Fraud opportunities for all Employees in Makassar Regional X Makassar.